Conditional inclusivity. 20 Conversations about current issues within the LGBTQ+ community - Michelekakis, Orestis (Homo Virtualis, 2025)
The LGBTQ+ community is often treated as a unified group, yet -upon closer inspection- the conflicts and discrepancies within begin to show. This paper attempts to examine whether LGBTQ+ individuals in Greece feel included within the community and, if not, suggest possible reasons behind their detachment. 20 members of the LGBTQ+ community participated in semi-structured interviews, which were subsequently analyzed via Interpretive Phenomenological Analysis (IPA), resulting in seven fundamental themes that shape the current state of the community; contested identity, the importance of physical appearance, political correctness, elitism, toxicity, labelling and the stance towards the heterosexual population. Despite those issues, however, a deeper emotional connection to the community -or the idea of one- seems to persevere.